Geometry of the overview - Polus-Rogalska, Katarzyna (Folia Philosophica, 2000)
The present article has shown the possible „appearances” of the world and the laws that govern their being seen in so many different ways. The whole discipline that examines objects in this way has been called here „the geometry of the overview". Only some of the statements contained in the article have their philosophical precursors. Most of them, such as the principle of half-seeing, of laevorotatory (or dextrorotatory) seeing, or the principle of trilateral seeing, are derived from the author’s own observations, and she is the author of both their names and their description. It seems that the study of the world in the suggested context is by no means complete and requires further specifications.